2012
DOI: 10.4028/www.scientific.net/msf.715-716.340
|View full text |Cite
|
Sign up to set email alerts
|

Grain Size Control in the Weld Pool and Heat Affected Zone Using Holograms

Abstract: Abstract. This paper considers the use of Holographic Optical Elements (HOEs) to shape the weld beam and hence control the grain size of the weld bead and the grain growth and phase transformations in the HAZ. Welds have been produced on carbon steel with the introduction of a nickel based filler powder, using different energy densities produced by the HOEs. Cross sections of the welds have been analysed in terms of the weld profile, weld pool shape and grain size in the deposit and the HAZ. Electron BackScatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…HOE's have previously been used to investigate laser welding and powder-bed laser cladding (Kell et al 2011;Higginson et al 2010;Kell 2007;Higginson et al 2012), experimenting with complex, asymmetrical beam profiles for thermal control. This research has included placing additional heat concentrations in different parts of the beam, as well as the addition of thermal ramps for pre-and post-heating.…”
Section: Introductionmentioning
confidence: 99%
“…HOE's have previously been used to investigate laser welding and powder-bed laser cladding (Kell et al 2011;Higginson et al 2010;Kell 2007;Higginson et al 2012), experimenting with complex, asymmetrical beam profiles for thermal control. This research has included placing additional heat concentrations in different parts of the beam, as well as the addition of thermal ramps for pre-and post-heating.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, holographic optical elements, kinoforms which can be used to create customised laser beam profiles, have been studied by Kell et al for laser welding [26], Higginson et al for laser powder bed fusion (L-PBF) [27] and Goffin et al for wire-fed laser cladding [28] and thin-film surface annealing [29]. The majority of these studies focused on metallurgical improvements, however, Goffin et al also found that alterations in the beam profile allowed the creation of wire clad tracks with beam power requirements reduced by 30% for an enlarged gaussian beam and 50% for a square uniform beam.…”
Section: Energy Modelling In Laser Systemsmentioning
confidence: 99%
“…This means that the standard methodology of trying to achieve the best possible result with a given laser beam no longer applies; the desired result can be specified first and then a HOE created to give the required laser beam thermal profile. Previous HOE research has shown positive results in the areas of laser welding, 24,25 where complex asymmetrical beam profiles were used to create wide uniform weld tracks; powder-bed laser cladding, 26 where they were used to control fluid flow and grain growth; wire-based laser deposition, 27,28 to control dilution and increase energy efficiency; and initial work on laser annealing. 29 The ability of holographic optics to control heat flow means that heat transfer simulations can then take on a powerful role in the optimization of experimental design.…”
Section: B Holographic Optical Elements In Laser Materials Processingmentioning
confidence: 99%